The Biological Disease-Modifying Antirheumatic Drugs and the Risk of Cardiovascular Events: A Systematic Review and Meta-Analysis - Suiyuan Hu; Chu Lin; Xiaoling Cai; Xingyun Zhu; Fang Lv; Lin Nie; Linong Ji (Mediators of Inflammation)
Objective. To assess the association between the use of biological disease-modifying antirheumatic drugs (bDMARDs) and the risk of cardiovascular events in patients with systemic inflammatory conditions. Methods. Eligible cohort studies or randomized controlled trials (RCTs) from inception to January 2021 were included. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) for cardiovascular outcomes were calculated in the fixed- and random-effects model accordingly. Associated factors with risks of cardiovascular events were also studied in sensitivity analyses and metaregression analyses. Results. Compared with non-bDMARD users, the risks of myocardial infarction (MI) (OR=0.74, 95% CI, 0.63 to 0.87), heart failure (OR=0.84, 95% CI, 0.74 to 0.95), cardiovascular (CV) death (OR=0.62, 95% CI, 0.40 to 0.95), all-cause mortality (OR=0.64, 95% CI, 0.58 to 0.70), and 3P-MACE (composite endpoint of MI, stroke, and CV death) (OR=0.69, 95% CI, 0.53 to 0.89) were significantly reduced in bDMARD users, which were mainly driven by the risk reduction in patients with rheumatoid arthritis (RA). TNF-α inhibitors exhibited consistent benefits in reducing the risks of MI, heart failure, CV death, all-cause mortality, and 3P-MACE. Moreover, the risks of heart failure, CV death, all-cause mortality, and 3P-MACE were significantly reduced in bDMARD users with follow-up over one year. Conclusions. The use of bDMARDs might be associated with the reduced risks of CV events, especially in patients with RA. The CV events might be less frequent in bDMARD users with TNF-α inhibitors or follow-up over one year. More investigations are needed to validate conclusions.